2007
DOI: 10.1007/s10509-007-9688-0
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear stability in the generalised photogravitational restricted three body problem with Poynting-Robertson drag

Abstract: The Nonlinear stability of triangular equilibrium points has been discussed in the generalised photogravitational restricted three body problem with Poynting-Robertson drag. The problem is generalised in the sense that smaller primary is supposed to be an oblate spheroid. The bigger primary is considered as radiating. We have performed first and second order normalization of the Hamiltonian of the problem. We have applied KAM theorem to examine the condition of non-linear stability. We have found three critica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 17 publications
3
20
0
Order By: Relevance
“…They have considered the smaller primary as an oblate body and bigger one as radiating and they have concluded that the triangular equilibrium points are unstable in linear sense. [16] has discussed the nonlinear stability in the generalized restricted three body problem with Poynting Robertson drag considering smaller primary as an oblate body and bigger one radiating. They have proved that the triangular points are stable in nonlinear sense.…”
Section: Introductionmentioning
confidence: 99%
“…They have considered the smaller primary as an oblate body and bigger one as radiating and they have concluded that the triangular equilibrium points are unstable in linear sense. [16] has discussed the nonlinear stability in the generalized restricted three body problem with Poynting Robertson drag considering smaller primary as an oblate body and bigger one radiating. They have proved that the triangular points are stable in nonlinear sense.…”
Section: Introductionmentioning
confidence: 99%
“…Ishwar and Kushvah (2006) examined the linear stability of triangular equilibrium points in the generalized photogravitational restricted three body problem with PoyntingRobertson drag, L 4 and L 5 points became unstable due to P-R drag which is very remarkable and important, where as they are linearly stable in classical problem when 0 < μ < μ Routh = 0.0385201. Kushvah et al (2007aKushvah et al ( , 2007bKushvah et al ( , 2007c examined normalization of Hamiltonian they have also studied the nonlinear stability of triangular equilibrium points in the generalized photogravitational restricted three body problem with Poynting-Robertson drag, they have found that the triangular points are stable in the nonlinear sense except three critical mass ratios at which KAM theorem fails. Papadakis and Kanavos (2007) given numerical exploration of the photogravitaional restricted five-body problem.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of P-R drag on the existence and stability of libration points is dicussed by many authors as Chernikov [3]; Murray [20]; Kushvah et.al. [32]; Lhotka and Celletti [46]; Mishra et. al.…”
Section: Introductionmentioning
confidence: 99%